Analisis Jaringan Syaraf Tiruan Menggunakan Algoritma Hebb Rule Untuk Mengetahui Serta Diagnosa Penyakit pada Tanaman Cabai - Rahma Nasution, Luftia; Sofinah Harahap, Lailan; Kartika Dewi, Aulia (UNIVERSITAS SERAMBI MEKKAH, 2025)
Chili is a plant that belongs to plants that come from the solanacae family group (a type of eggplant tribe). The presence of plant diseases in chili plants can cause a decrease in chili production and even the death of chili plants. One of the causes of plant diseases is pathogenic fungi that can exist in seeds, soil, or air, even in vector insects. Diseases of chili plants due to pathogenic fungi are often difficult to overcome. This can be caused by, among other things, the degree of malignancy or fungus, the susceptibility level of the chili plant, and the support of appropriate environmental factors. Therefore, it is necessary to recognize every chili plant disease due to many causes so that decisions can be made to prevent or manage it appropriately. Therefore, the method used in analyzing the diagnosis in chili plants is the hebb rule method algorithm where this method regulates the weight value where this weight will process the completion of the diagnosis.